(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article analyzes the space of spiritual and moral education in modern education. Analyzing the main approaches to understanding spirituality, the authors reveal the essence of spiritual and moral education, which makes it possible to determine its subject.